Meningkatkan Peran Industri dalam Pengelolaan Utang dan Penanganan Global Warming - Sunita Dasman; Supriyanto Supriyanto; Fiqih Maria; Erin Soleha; Indra Setiawan (Jurnal Pelita Pengabdian, 2025)
The industry plays a central role as the primary driver of the global economy and has significant potential to reduce carbon emissions through technological innovation, energy efficiency, and transitioning to a low-carbon economy. However, financial challenges often become major obstacles in realizing technological innovation transformation. Wise debt management is necessary to ensure the operational sustainability of industries while supporting investments in green initiatives. The initial situational analysis required includes: 1) Identifying the company’s debt profile and repayment capacity, 2) Conducting an inventory of greenhouse gas (GHG) emissions generated by industrial operations, 3) Structuring opportunities for the use of renewable energy and low-carbon technologies. Companies need to establish internal policies to redirect debt refinancing to instruments that support sustainability, such as green bonds or sustainability-linked loans. They should also set carbon emission reduction targets for the short, medium, and long term. Optimizing the use of a "Green Crowdfunding Platform" that connects companies with investors interested in funding environmentally friendly projects through application-based technology is crucial. Environmental management requires the involvement of all stakeholders, including the government, industry, academics, communities, and the media.